2019
DOI: 10.1016/j.jjcc.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

High-grade patent foramen ovale is a risk factor of unprovoked decompression sickness in recreational divers

Abstract: Background: Patent foramen ovale (PFO), male sex, age, and body mass index (BMI) were all identified as potential risk factors of decompression sickness (DCS). It has been debated whether PFO might cause unprovoked DCS (i.e. without violation of decompression procedure) due to paradoxical embolization of venous gas emboli. To date, there are no data on the incidence or risk factors of unprovoked DCS. This study sought to evaluate the risk factors of unprovoked DCS in recreational divers. Methods: A total of 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In a previous report from the DIVE-PFO, we have demonstrated that a high-grade PFO was a major risk factor for unprovoked DCS in 489 recreational scuba divers (22). This study specifi cally focused on recreational diving only and 7 % of the divers suffered from an unprovoked DCS.…”
Section: Discussionmentioning
confidence: 86%
“…In a previous report from the DIVE-PFO, we have demonstrated that a high-grade PFO was a major risk factor for unprovoked DCS in 489 recreational scuba divers (22). This study specifi cally focused on recreational diving only and 7 % of the divers suffered from an unprovoked DCS.…”
Section: Discussionmentioning
confidence: 86%
“…In brief, on the one hand, it has traditionally been considered that DCS with cerebral involvement would be due to the predominant involvement of the arterial circulation (stroke-like radiological imaging) [ 5 , 9 ], by paradoxical embolism in patients with patent foramen ovale (PFO) or by opening of pulmonary arterio-venous shunts in the case of large venous embolisms where the alveolar–capillary filter is exceeded [ 5 , 8 ]. Thus, previous studies have shown that the presence of a right-to-left shunt, as in the case of a PFO, significantly increases the risk of DCS in compressed-gas diving by facilitating a paradoxical pathway of arterial embolism [ 10 , 11 , 12 , 13 ]. This facilitating effect of the development of DCS, related to the right-to-left shunt, has also been suggested in some cases in breath-hold divers [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PFO grade 3 was significantly associated with unprovoked DCS episode in professional SCUBA divers. 27 …”
Section: Pfo Presence and The Risk For DCImentioning
confidence: 99%